Carbapenem Resistance Mechanisms in Acinetobacter baumannii: Spotlight on OXA Genes - Jasim, Muhammad Kareem; Hadi, Zainab Jaber; Alsherees, Hashim Ali Abdualmeer; Annooz, Aaedah (Medical Science Journal for Advance Research, 2023)
Acinetobacter baumannii is a highly problematic bacterium due to its multidrug-resistant nature and ability to rapidly develop resistance. Carbapenem-resistant A. baumannii (CRAB) is particularly concerning, recognized as a top priority pathogen by the World Health Organization (WHO). In this study, we aimed to assess the susceptibility of A. baumannii to antibiotics and characterize the presence of specific carbapenem resistance genes using PCR analysis. The study was conducted as a cross-sectional investigation at Al-Sader Medical City and Baghdad Teaching Hospitals between October 2022 and February 2023. A total of 59 A.baumannii isolates were collected from patients. To ensure accuracy in diagnosis, the isolates underwent thorough processing using morphological techniques, biochemical tests, and Vitek2 systems. The susceptibility of the isolates to 24 antibiotics was evaluated using the Kirby-Bauer method. Additionally, DNA extraction and PCR analysis were performed to detect the presence of carbapenem resistance genes. The study included analysis of 59 specimens collected from patients, including sputum, wound swabs, blood, and inguinal swabs. The majority of the isolates were obtained from in-patients, demonstrating a significant difference compared to outpatients. Among the studied isolates, the most prevalent carbapenem resistance gene detected was blaOXA51, present in 97% of the isolates. This highlights the substantial presence of blaOXA-mediated carbapenem resistance among A. baumannii strains in our study population. Furthermore, our findings revealed alarmingly high resistance rates against the majority of antibiotics commonly used to treat A. baumannii infections. Approximately 95% of the isolates were classified as extensively drug-resistant, indicating resistance to multiple classes of antibiotics. This poses significant challenges in terms of effective treatment options and emphasizes the urgent need for alternative strategies to manage A. baumannii infections.